Cohort Study of Features Used by Experts to Diagnose Transient Ischemic Attack. (October 2020) - Fitzpatrick, Tess; Gocan, Sophia; Wang, Chu Qi; Bourgoin, Aline; Taljaard, Monica; Cheng, Wei; Dowlatshahi, Dar; Stotts, Grant; Shamy, Michel
Background and Purpose: The diagnosis of transient ischemic attack (TIA) is largely dependent on a process of clinical decision-making that remains poorly characterized in the absence of a validated and accessible biomarker or imaging test. We performed a retrospective chart review to identify variables associated with a final neurologist diagnosis of TIA/stroke. Methods: Records for all patients seen in The Ottawa Hospital's Stroke Prevention Clinic in 2015 were analyzed for patient and referral characteristics, features of the presenting neurological event, and final diagnosis by a stroke neurologist (classified as definite, possible, or definite not TIA/stroke). Multinomial logistic regression analysis with backward elimination was used to identify variables associated with the final diagnosis. Results: Our inclusion criteria were met by 1894 patients. After backward elimination, 23 potentially important variables were identified, including monocular vision loss (odds ratio [OR]: 30.4, 95% confidence interval [CI]: 14.6-63.3), symptoms of sudden onset (OR: 28.3, 95% CI: 14.2-56.2), unilateral weakness affecting 2 or 3 of face, arm, or leg (OR: 17.7, 95% CI: 9.8-31.7), and homonymous hemianopia (OR: 16.6, 95% CI: 8.1-34.0). Conclusions: Accurate diagnosis of TIA is essential to initiating appropriate secondary stroke prevention therapies. A focus on elements of the patient history most commonly associated with a final diagnosis of TIA/stroke may help to identify patients in greatest need of urgent SPC assessment and allow for the provision of effective and efficient stroke prevention services.